Edible vegetable Roktoshirinchi (Achyranthes ferruginea Roxb.) ameliorates pain and inflammation in experimental animal model - Reza, A S M Ali (IIUC Studies, 2023)
Achyranthes ferruginea, a plant commonly used in Bangladeshi traditional medicine, was investigated in this study to uncover new therapeutic applications. The research focused on assessing it’s in vitro anti-inflammatory properties and in vivo analgesic effects using a methanol extract. In vitro, the methanol extract of Achyranthes ferruginea was examined for its anti-inflammatory effects through membrane stabilization and protein denaturation tests using Human Red Blood Cells (HRBCs). The results indicated a moderate dose-dependent anti-inflammatory effect, with maximum inhibitions of 34.5% (protein denaturation) and 53.68% (membrane stability) at a concentration of 1000 μg/ml For in vivo assessments, Swiss albino mice were utilized, with Diclofenac Sodium as a positive control. The extract demonstrated significant dose-dependent analgesic effects in both chemically induced paw licking and writhing tests. Furthermore, molecular docking studies revealed a higher binding affinity of N-trans-feruloyl-4'-O-methyldopamine with COX-1 and COX-2 enzymes. Overall, Achyranthes ferruginea methanol extract exhibited moderate anti-inflammatory activity and robust analgesic properties, highlighting its potential therapeutic applications. IIUC Studies, Vol.-20, Issue-1, June 2023, pp. 109-120